Biosorption of nickel and cadmium using Pachira aquatica Aubl. peel biochar - Talita L. S. Nascimento; Karine F. S. Oliveira; Joemil O. D. Junior; Alexandre S. Pimenta; Dulce M. A. Melo; Marcus A. F. Melo; Renata M. Braga (Scientific Reports, 2024)
Abstract This study aimed to assess the value of Pachira aquatica Aubl. fruit peels by exploring their applicability in the biosorption process for the removal of Ni(II) and Cd(II) metal ions. The Pachira aquatica Aubl. fruit peel biochar (PAB) was extensively characterized through various techniques, including proximate analysis, helium pycnometer, XRD, SEM, point of zero charge determination, zeta potential measurement, and Boehm titration. Subsequently, kinetic, isotherm, and thermodynamic batch biosorption studies were conducted, followed by column biosorption tests. The characteristics of PAB, including low moisture content, a neutral point of zero charge, porosity, an irregular and heterogeneous structure, a negatively charged surface, and the presence of functional groups, indicate its remarkable capacity for efficiently binding with heavy metals. Biosorption equilibrium time was achieved at 300 min for both ions, fitting well with a pseudo second-order kinetic model and Langmuir isotherm model. These data suggest that the biosorption process occurred chemically in monolayer. The column C presented an exhaust volume of 1200 mL for Ni(II) and 1080 for Cd(II) and removal of 98% and 99% of removal for Ni(II) and Cd(II), respectively. In summary, PAB demonstrates substantial potential as a biosorbent for effectively removing heavy metals, making a valuable contribution to the valorization of this co-product and the mitigation of environmental pollution.